The Study of Cultural Heritage Tourism: Ban Prang Ban Nakhon, Prang Sub District, Khong District, Nakhon Ratchasima Province - buddalerd, patlapa (Journal of Management Science Nakhonratchasima University, 2025)
This qualitative research aimed to: 1) explore the cultural heritage tourism sites, 2) study the values of cultural heritage tourism, and 3) identify the sustainable management approaches for cultural heritage tourism. The study was conducted in Ban Prang Nakhon, Khong District, Nakhon Ratchasima Province. The sample group consisted of 20 participants selected through purposive sampling. These included tourism experts from both public and private sectors, local leaders, and community members involved in tourism development. The primary research instrument was an open-ended interview form. The findings revealed that: 1) the community possessed significant potential to be developed as a the cultural heritage tourism destination. However, it lacked the systematic tourism management and appropriate funding support. The guidelines for developing the community as a cultural heritage tourism destination included improving the management system, increasing financial support, promoting tourism activities, enhancing tourism information and databases, upgrading basic infrastructure, and organizing activities that are attractive to tourists. Moreover, the sustainable cultural heritage tourism management in Ban Prang Nakhon should also involve the community participation in the conservation of the ancient castle and local culture. 2) the values of cultural heritage tourism identified in the area included the economic value, the historical value, the artistic value, the traditions and local cultural lifestyles. 3) the sustainable cultural heritage tourism management should focus on developing the area surrounding the ancient castle into a cultural tourism site, emphasizing the preservation and transmission of local culture, building community networks to safeguard the castle and cultural heritage, and encouraging active participation from both government agencies and private organizations in promoting tourism and preserving local culture.